Professionalism, Staff Competency and Financial Reporting Quality in The Public Sector (Malaysian Management Journal, 2019)
The financial reporting quality (FRQ) refers to better information dissemination across different users. It is a critical phenomenon for gauging organizations’ performance and survival. In many countries, the public sector has witnessed considerable changes in the past decade. The prominent one is the international public sector accounting standards (IPSAS) for the public sector entities. Drawing on contingency and institutional theories, this study tests the effects of professionalism on the relationship between staff competency and FRQ under the new accounting standards. By using a survey research approach and self-administered questionnaire, data was gathered from 118 directors of finance that represents the local governments of four states in the north-west geopolitical zone of Nigeria. The Partial Least Squares Structural Equation Modeling (PLS-SEM) estimate revealed a significant positive relationship between staff competence and FRQ. Conversely, no significant effect was found in the interaction of professionalism on the model. The implications from the study are discussed in the context of Nigeria.